THE CONTEMPORARY CONCEPT OF CHILDHOOD:INSTITUTIONALIZATION, FAMILIALIZATION AND INDIVIDUA(LIZA)TION - Jerončić, Milica М (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
The author of this paper is analyzing the contemporary concept of childhood, regarding the predominant opinions, relationships and activities concerning children. The aforementioned is the result of changes in the perception of childhood in societies of (late) modernity and, in particular, the consequences of the social processes of institutionalization, familialization, individualization and the individuation of childhood itself. Institutionalization and familialization stands for a process of enclosing children  in the „children's world“, meaning that the daily life of children is spatially and timely placed in social institutions intended for children, or in the home, indicating their segregation and numerous  limitations for the sake of child protection and control. On the other side, there is a parallel process of childhood individualization which shows children as unique social actors, who have their individual rights and obligations -process of childhood individuation- in which the UN Convention of the Rights of the Child has a central point. However, these processes are characterized by limited domain of influence and paradoxes as a result of opposite processes of institutionalization and the familialization of childhood. The impact and the significance of the above mentioned social processes, as well as their interconnection,  are (re)defining the contemporary childhood. The author is pointing at the insignia, but also at the contradictory and contradictions of these processes, which result in great controversies and a marginalized position of children in the contemporary, „child-centred“ society.
Keywords: individuation; individualization; familialization; sociology of childhood; institutionalization